Antimicrobial efficiency of rosemary, thyme and clove essential oils on the preservation of marinated chicken breasts (fillets) - Demir, Pelin; Aydemir, Mehmet Emin; Alan, Selcuk; Oksuztepe, Gulsum (Univ Zulia, Facultad Ciencias Veterinarias, 2024)
Essential oils can be used as natural preservatives in the poultry meat industry. The aim of this research was to determine the effect of some essential oils on the microbial, physicochemical, and sensory properties of marinated chicken breast. For this purpose, rosemary, thyme, and clove essential oils were used at doses of 125 mgkg-1-1 and 250 mgkg-1-1 while marinating chicken breasts. After the marinated chicken breasts were divided into groups, they were stored in the refrigerator at 4 degrees C. degrees C. The results showed that 250 mgkg-1-1 doses of essential oils, especially at 24 h, and rosemary had more inhibitory effects on some microbial (total mesophilic aerobic, total psychrophilic aerobic, and yeast-mold) parameters. However, the sensory groups with the addition of 125 mgkg-1-1 were more accepted. Among these groups, the most acceptable group was the group that added 125 mgkg-1-1 of thyme essential oil. The study shows that the use of thyme essential oil as an alternative to chemical preservatives may be beneficial both in extending the shelf life of marinated chicken breasts and in terms of consumer taste.
Eficacia antimicrobiana de los aceites esenciales de romero, tomillo y clavo en la conservación de pechugas de pollo marinadas (filetes)
Keywords: Essential oil compounds; marination; chicken breast; preservation; quality parameters